Neuroeconomics of prosocial behavior : the compassionate egoist - Declerck, Carolyn; Boone, Christophe (Academic Press, 2016)
"This summary of recent research in neuroeconomics aims to explain how and why a person can sometimes be generous, helpful, and cooperative, yet other times behave in a self-interested and/or exploitative manner. The book explains a dual process of analysis measuring immediate needs of the individual, relative to long term gains possible through prosocial behavior (e.g. synergy, accumulating profits, (in)direct reciprocity) with the output further mitigated by the motivation of the individual at that moment and any special circumstances of the environment. Ultimately it can be shown that prosocial behavior can be economically rational. Yet even when individuals are intrinsically motivated to act prosocially, they are also able to reverse this behavior when they sense it is no longer adaptive."--